Application of Grey System Theory and Entropy Weight Method in Basketball League Matches - Yibing Wei; Tuolei Zhao (International Journal of Engineering and Management Research, 2019)
The basketball league issue has always been a concern, and the predictions for each team's next game have also attracted the attention of the audience. Now more and more fans have begun to predict the future of the favorite team. By analyzing the score data of some teams in the past, this paper obtains the appropriate prediction function by constructing the grey system theory model, and then predicts the future performance of the team. At the same time, using the idea of entropy weight method, through the measurement of the weight of each team in a basketball game, and using the idea of combining numbers and figures, the level of each team is qualitatively analyzed through the weight map.